Analysis of the determinants of cash holdings and the implications for local government spending effectiveness in West Java - Randos, Ismail Marzuki; Suciyati, Nia (Journal of Accounting Auditing and Business, 2026)
Cash management is fundamental to sustaining uninterrupted local service delivery and supporting credible budget execution. In West Java, municipal cash holdings exhibited fluctuations over 2019–2023, with only a limited number of districts/cities consistently maintaining cash holdings ratios above the operational sufficiency threshold. This study examines (i) the determinants of cash holdings Capacity and (ii) the relationship between cash holdings and expenditure effectiveness. Cash Holdings Capacity is classified as sufficient when the cash holdings ratio exceeds 100%, whereas Expenditure Effectiveness is classified as effective when the effectiveness ratio exceeds 90%. The quantitative analysis applies binary logistic regression to 27 districts/cities in West Java for the 2021–2023 period. The results indicate that cash sufficiency is associated with a combination of regional characteristics, governance-related conditions, and financial fundamentals, including population and area size, audit findings, short-term solvency, and revenue stability. In addition, the second model shows that higher cash holdings are significantly related to lower expenditure effectiveness, suggesting that cash accumulation may coincide with delays in budget absorption and spending execution rather than signalling superior fiscal performance. The study suggests that improving local cash outcomes requires a dual focus: strengthening liquidity fundamentals and revenue predictability while simultaneously enhancing institutional capacity to translate available cash into timely, effective expenditure.